Vietnam : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper on Vietnam analyzes interest rate policy under credit control. There are a number of issues involved in setting interest rates in the presence of bank-by-bank credit ceilings that do not arise in other controls. In Vietnam, as macroeconomic stabilization has taken hold, the inconsistencies of an administratively controlled financial system are becoming more evident. This points to the importance of moving quickly to develop additional policy tools so that interest rate policy can be freed from the tradeoffs being faced, allowing different policy objectives to be pursued independently.